Immunoaffinity concentration and purification of waterborne enteric viruses for detection by reverse transcriptase PCR. - Schwab, K J (1996)
To assess the risks from viral contamination of drinking-water supplies, there is a clear need for methods to directly detect viral pathogens. In this study, we developed a broad-spectrum immunocapture method for concentration and purification of enteric viruses. The method involved indirect antibody capture (AbCap) of intact viruses followed by release of virion genomic RNA and reverse transcriptase PCR for amplification and oligoprobe hybridization for detection. The procedure involved concentrating enteric viruses from large volumes of water by standard filtration-elution techniques with IMDS filters and 1 liter of 1% beef extract-0.05 M glycine (BE/G) as an eluate. The BE/G eluate was concentrated and purified by polyethylene glycol (PEG) precipitation, Pro-Cipitate (a commercially available protein precipitating reagent) precipitation, and a second PEG precipitation to a volume of approximately 500 mu l. Aliquots of the second PEG precipitate were further processed by RNA extraction, AbCap, or cell culture analysis for infectious viruses. The AbCap method was applied to 11 field samples of fecally contaminated surface water. Of the 11 samples, 9 were positive for enteric viruses by AbCap method 4 of 11 samples were positive for enteric viruses by direct RNA extraction of a small aliquot of the second PEG concentrate; and 4 of 11 samples were positive for enteric viruses by measurement of cell culture infectivity. The results of enteric viruses were compared with those for standard bacterial and coliphage indicators of fecal contamination.